Automatic ID Consultation for Inpatients With COVID-19: Point, Counterpoint, and a Single-Center Experience. (11th August 2020) - Nguyen, Cynthia T; Olson, Gregory; Pho, Mai T; Lew, Alison K; Pitrak, David; Saltzman, Jina; Hazra, Aniruddha; Pursell, Kenneth; Pettit, Natasha N
Abstract: There are many unknowns with regard to COVID-19 clinical management, including the role of Infectious Diseases Consultation (IDC). As hospitalizations for COVID-19 continue, hospitals are assessing how to optimally and efficiently manage COVID-19 inpatients. Typically, primary teams must determine when IDC is appropriate, and ID clinicians provide consultation upon request of the primary team. IDC has been shown to be beneficial for many conditions; however, the impact of IDC for COVID-19 is unknown. Herein, we discuss the potential benefits and pitfalls of automatic IDC for COVID-19 inpatients. Important considerations include the quality of care provided, allocation and optimization of resources, and clinician satisfaction. Finally, we describe how automatic IDC changed throughout the COVID-19 pandemic at a single academic medical center.